Alzheimer's-related peptide amyloid-β plays a conserved role in angiogenesis. - D Joshua Cameron; Cooper Galvin; Tursun Alkam; Harpreet Sidhu; John Ellison; Salvadore Luna; Douglas W Ethell (PLoS ONE)
Alzheimer's disease research has been at an impasse in recent years with lingering questions about the involvement of Amyloid-β (Aβ). Early versions of the amyloid hypothesis considered Aβ something of an undesirable byproduct of APP processing that wreaks havoc on the human neocortex, yet evolutionary conservation--over three hundred million years--indicates this peptide plays an important biological role in survival and reproductive fitness. Here we describe how Aβ regulates blood vessel branching in tissues as varied as human umbilical vein and zebrafish hindbrain. High physiological concentrations of Aβ monomer induced angiogenesis by a conserved mechanism that blocks γ-secretase processing of a Notch intermediate, NEXT, and reduces the expression of downstream Notch target genes. Our findings allude to an integration of signaling pathways that utilize γ-secretase activity, which may have significant implications for our understanding of Alzheimer's pathogenesis vis-à-vis vascular changes that set the stage for ensuing neurodegeneration.